Chapter 11 Three Markets and Three Types of Competitiveness Pulp and Paper Industry - Kurosawa, Takafumi (Taylor & Francis, 2017)
Paper is a universal and familiar product for any industrial society. Although digitization eroded its dominance as an information carrier, one can hardly live without paper's use in printing, packaging and wrapping material, sanitary products, and a variety of industrial materials. Paper has over 2,000 years of history and has been consumed in virtually all regions of the world. On the supply side, almost all major industrial nations have a paper industry. These features make it an ideal object of long-term historical analysis of the industry-specific patterns of competitiveness.